MEMBANGUN KESETARAAN GENDER DALAM KEHIDUPAN KELUARGA PASANGAN PEKERJA: ANALISIS KONSTRUKSI-NORMATIF - Aeni, Nurul; Sadari, Sadari (Asosiasi Dosen PTKIS Indonesia, 2023)
The issue of gender equality is often an interesting issue to be studied in various spheres of life both in the public sphere and in the domestic sphere. In good family life is determined by the life partner himself. There are families who decide on the husband as the head of the family and work to support the family and the wife remains at home carrying out her domestic obligations such as cooking, child care and other domestic obligations. There are also families where the wife is the backbone of the family, the wife works outside the home to provide for her family and the husband supports the wife to help with her domestic obligations, there are also families that live together between husband and wife work both ways. In this paper will be studied how the concept of gender equality, how to build gender equality in family life where married couples both work in constructive and normative analysis. The results of this study found several points. First, gender injustice that occurs is caused by culture that is constructed in society. Second, gender injustice in family life still occurs and the forms of gender injustice include marginalization, subordination, stereotypes, violence and double burden. Third, three working couples who were informants in this study in their family lives experienced gender injustice, namely double barden, but even so the family remained happy because their main role in the family was carried out responsibly. Gender equality in the family of working couples must be realized through strengthening the fair division of roles between men and women in the family in accordance with Law Number 1 of 1974 concerning marriage and the Compilation of Islamic Law.